Kebijakan Hukum Pidana Dalam Menanggulangi Tindak Pidana Illegal Logging Menurut Undang-Undang Nomor 41 Tahun 1999 Tentang Kehutanan - Nur Abdi, Andika; Syahruddin, Erwin (Jurnal Pro Hukum : Jurnal Penelitian Bidang Hukum Universitas Gresik, 2022)
Criminal law policy essentially contains state policies in regulating and limiting power. In anticipating efforts to tackle the crime of Illegal Logging , it is very important to carry out a criminal law policy, especially legislative policy (formulation policy), namely how to formulate an act that is considered a criminal act of illegal logging. The research method used is the normative juridical method.crimes illegal logging according to Law Number 41 of 1999 concerning Forestry is listed in Article 50 while the criminal provisions are listed in Article 78. The criminal law policy in tackling the crime of illegal logging at this time is by carrying out a formulation policy against theCriminal illegal logging, Code, Law Number 5 of 1990 concerning Conservation of Biological Natural Resources and Their Ecosystems, Law Number 41 of 1999 as amended by Law Number 19 of 2004 concerning Stipulation of Government Regulation in Lieu of Law Number 1 of 2004 concerning Amendment to Law Number 41 of 1999 concerning Forestry into Law and Law Number 18 of 2013 concerning Prevention and Eradication Forest Destruction.